2015
DOI: 10.1016/j.eurpsy.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Childhood abuse in the etiological continuum underlying psychosis from first-episode psychosis to psychotic experiences

Abstract: 2 AbstractPurpose: The present study aimed to extend the literature on childhood trauma and psychosis examining the impact of child abuse across the continuum of psychosis, from subclinical psychosis to first episode of psychosis (FEP). Methods:The study included a total of 198 individuals divided in three groups: 1) 48 FEP patients, 2) 77 individuals scoring above the 75 th percentile in the Community Assessment of Psychic Experiences (CAPE (1)) which were classified as "High CAPE" group; and 3) 73 individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
2
0
1
Order By: Relevance
“…In the short time since the publication of that review, over twenty additional studies have been published, most of which provide further evidence that childhood adversities are more common among those with psychosis, again across the spectrum. Perhaps most notably, in a prospective study of 1,112 adolescents, Kelleher et al found that cessation of trauma was associated with subsequent cessation of psychotic experiences.…”
Section: Evidencementioning
confidence: 99%
“…In the short time since the publication of that review, over twenty additional studies have been published, most of which provide further evidence that childhood adversities are more common among those with psychosis, again across the spectrum. Perhaps most notably, in a prospective study of 1,112 adolescents, Kelleher et al found that cessation of trauma was associated with subsequent cessation of psychotic experiences.…”
Section: Evidencementioning
confidence: 99%
“…2006, Modinos ve ark. 2010, Alemany ve ark. 2015 kullanılan gruplandırma yöntemine benzer biçimde örneklem yeniden gruplandırılmıştır.…”
Section: Gruplar Ve Değişkenlerunclassified
“…Studies examining a possible association between TLEs, symptoms and functional outcomes have yielded unclear results. Although some studies found evidence of a relationship between TLEs and positive symptoms (Ajnakina et al, 2016;Alemany et al, 2015;Duhig et al, 2015), others have failed to find any association (Janssen et al, 2004;van Nierop et al, 2014). Likewise, some studies reported more clinical severity in people with psychosis that reported having suffered TLEs (Aas et al, 2016;Ajnakina et al, 2016), but not others (Haahr et al, 2018;Lindgren et al, 2017;Trotta et al, 2016).…”
Section: Introductionmentioning
confidence: 99%